Abandoned object detection with video surveillance - Aurangzeb, Chowdhury Farsad; Shanchary, Israt Jahan; Tasdid, Salman (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2014.